Edukasi Gerakan Cuci Tangan Pakai Sabun Sebagai Pencegahan Transmisi Penyakit pada Anak Usia Sekolah di SD IT Insan Qur’ani - Haedar Putra; Evi Gustia Kesuma; Nurul Istiqamah Mantika; Bayu Anugrah Putra; Herma Lestari; Liana Safitri (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Preschool aged children have a habit of paying less attention to hand washing behavior, especially in the play environment. The habit of washing hands with soap (CTPS) is still a global concern because people still forget to wash their hands. The focus of CTPS activities is early childhood because they are the ones who will be agents of change in the future. In this activity, hand washing education with soap will be provided to children in the form of counseling indoors and followed by simulations in the field based on the 7 steps for washing hands. Before carrying out the activity, they did not know how to wash their hands with soap properly and correctly. So this activity was considered 100% successful, this was because the children were able to practice washing their hands using soap properly and correctly. Implementation time is October 2023. The aim of this activity is to provide positive information to increase preschool age children's knowledge regarding clean living behavior, especially regarding hand washing, so that children are better able to maintain personal hygiene at school and avoid disease. Activities were carried out for pre-school children at SD IT Insan Qur'ani.